Inovasi Desain Roster Beton dengan Mengutamakan Unsur Privacy dan Estetika - Arya Maulana Candra Rizky; Muh. Husaini Alfani Karuniawan; Riza Susanti; Shifa Fauziyah (Jurnal Sipil dan Arsitektur, 2024)
A roster is a nonstructural construction that plays a role in regulating the temperature and humidity of the air in the room; not only that, a roster is also often used as a room divider. The number of roster product designs on the market allows roster manufacturers to make products whose designs tend to prioritize less privacy and only prioritize aesthetic factors in the design of the roster structure. This research was conducted to create changes in roster design to improve the function of the roster, where the roster itself must have optimal air circulation and an element of privacy that is maintained. This research uses an experimental method by making its concrete roster design innovation and comparing it with existing products on the market; as a comparison, 2 product design samples were taken from the market and tested. Tests are carried out in the form of air circulation testing, facade testing, compressive strength testing, and water absorption testing. AutoDesk CFD software is used as a means for testing air circulation and as a success parameter for testing compressive strength and water absorption per SNI 03-1570-1989. The value of the air circulation test is 866343.0 cm3/s = 866.343 Liter/s for the 1st design, 842725.0 cm3/s = 842.725 Liter/s in the 2nd design, 7964661.0 cm3/s = 796.4661 Liter/s in the 3rd design. The compressive strength result obtained is 1.25 N/mm2. The results of the test values of compressive strength and water absorption show that they can meet the specified requirements. This concrete roster design innovation can make the right solution for consumers when choosing a more optimal concrete roster.